Cerebellar Herniation after Lumbar Puncture in Galactosemic Newborn - Kalay, Salih; Öztekin, Osman; Tezel, Gönül; Demirtaş, Hakan; Akçakuş, Mustafa; Oygür, Nihal (American Journal of Perinatology Reports, 2011)
Cerebral edema resulting in elevated intracranial pressure is a well-known complication of galactosemia. Lumbar puncture was performed for the diagnosis of clinically suspected bacterial meningitis. Herniation of cerebral tissue through the foramen magnum is not a common problem in neonatal intensive care units because of the open fontanelle in infants. We present the case of a 3-week-old infant with galactosemia who presented with signs of cerebellar herniation after lumbar puncture.
Keywords: Newborn; galactosemia; lumbar puncture; herniation